Comparative analysis of health policy implementation in toddler growth and development monitoring - Rika Suryani; Desmawati Desmawati; Afdal Afdal (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The toddler period, often referred to as the golden period, is critical for optimizing child growth and development. Based on Padang Health Office data (2024), Community Health Center Pemancungan achieved the highest performance in growth and development monitoring indicators, while Community health center Pauh recorded the lowest. Purpose: To comparatively analyze the implementation of health policies in toddler growth and development monitoring between Community health center Pemancungan and Community health center Pauh in Padang City. Method: A qualitative design using an input–process–output system approach. Informants included the mayor, head of the health office, heads of Community health center, program managers, regional supervisors, and Integrated health service post cadres. Data were collected through interviews, observation, and documentation, and analyzed using the Miles and Huberman method. Results: Policy implementation refers to Minister of Health Regulation No. 6 of 2024 on Minimum Service Standards and is operationalized through Integrated health service post activities, including weighing, height measurement, vitamin A supplementation, and developmental screening. Although Community health center Pauh has more human resources and facilities, utilization remains suboptimal. Both Community health center show gaps in implementation processes, particularly in adherence to standards, recording, and reporting. Output indicators indicate that monthly monitoring is conducted but has not yet achieved program targets. Conclusion: The implementation of toddler growth and development monitoring policies in both Community health center remains suboptimal. Strengthening planning, improving implementation quality, and reinforcing continuous monitoring and evaluation are essential to enhance program performance.